Siberian Exile in Russian Historiography of 1990s — 2010s - A. A. Ivanov; S. L. Kuras; T. L. Kurаs (Научный диалог)
The article is devoted to the analysis of modern Russian historiography of criminal and political exile to Siberia. The authors consistently consider the main directions of development of post-Soviet studies, note, first of all, the great interest of historians in various aspects of the penitentiary policy and practice of the empire in Siberia, the features of the imprisonment of political and criminal prisoners. Further, a sharp drop in the attention of specialists to the history of the exile of the Social Democrats, and above all, the Bolsheviks, is stated, and vice versa — a significant increase in works devoted to the stay in exile of representatives of the Socialist Revolutionaries and anarchists. The publications on the history of the exile to Siberia of the Decembrists are analyzed, the content of the discussion about the evolution of their worldview, the role of “noble revolutionaries” in the political his-tory of Russia is conveyed. The authors also briefly analyze the main directions of publications of the Irkutsk collection of scientific articles “Siberian Link”, created back in 1973. It is concluded that the history of criminal and political exile to Siberia as a scientific direction in the post-Soviet period continues to develop successfully, acquiring new facets, replenished with specific studies and authors.